Induced Genotoxicity in Nitrate‐Rich Water Treated With Medium‐Pressure Ultraviolet Processes. Issue 6 (1st June 2015) - Martijn, Bram J.; Kruithof, Joop C.; Hughes, Raeanna M.; Mastan, Raul A.; Van Rompay, R.; Malley, James P.
Abstract : Just as with chlorination, medium‐pressure (MP) ultraviolet (UV) treatment applied for disinfection purposes has been found to cause formation of genotoxic compounds, measured by the Ames test. By lowering the nitrate and dissolved organic carbon (DOC) content, the Ames test response was reduced substantially. The impact of nitrate photolysis on formation of genotoxic compounds was confirmed. A representative organic micro pollutant selection had no significant impact on the Ames test response. Formation of genotoxic compounds was found after MP UV disinfection, photolysis, and advanced oxidation of pretreated groundwater. In addition to nitrate and DOC content, aromaticity of organic matter had a strong impact. Ames test responses were converted into 4‐nitroquinoline oxide (4‐NQO) equivalent concentrations to enable quantitative comparison and to apply simple risk assessment. Based on the threshold for toxicological concern, already at doses applied for MP UV disinfection, the 4‐NQO equivalent concentration of formed genotoxic compounds in nitrate‐rich water exceeded the limit of no risk.